Anthelmintic resistance of selected goat farms in Terengganu - Abdul Aziz, Nor Azlina (Veterinary Association Malaysia, 2011)
A study was conducted to examine the current status of anthelmintic resistance of strongyles in goats raised in selected farms in Terengganu, Malaysia. The fecal egg count reduction test (FECRT) was performed with anthelmintics tested being benzimidazole, levamisole, ivermectin and closantel. Results indicated that all farms exhibited resistance towards benzimidazole and closantel while only two farms were still susceptible to levamisole and one farm exhibited suspected resistance to ivermectin. Four farms exhibited resistance to all anthelmintics tested. The strongyles which had developed anthelmintic resistance were predominantly Haemonchus contortus followed by Trichostrongylus spp. Results obtained from this study provide further evidence that anthelmintic resistance is escalating and the need for effective action is very important for the small ruminant industry.